Optimization of numerical models through instrumentation data integration: Digital twin models for dams. Issue 6 (1st November 2021) - Conde López, Eduardo R.; Toledo Municio, Miguel Ángel; Salete Casino, Eduardo
Abstract: Dam safety is a relevant aspect in our society due to the importance of its functions (power generation, water supply, lamination of floods) and due to the potentially catastrophic consequences of a serious breakdown or breakage. Dam safety analyses are fundamentally based on behavior models, which are idealizations of the dam‐foundation that allow us to calculate the dam's response to a certain combination of actions. The comparison of this response with the real one, measured by the auscultation or survey devices, is the main element to determine the safety status of the structure. To improve this analysis, it is necessary to increase the accuracy of the numerical models obtaining a digital twin that allows knowing, in a faithful way, how the structure is going to work in normal and extreme situations.